The role of the Iliopsoas in the transition from walking to running - Camila Taira; Ryoji Kiyama; Arturo Forner-Cordero (European Journal of Human Movement, 2025)
Muscle activation changes may be one of the mechanisms that elicit the walk-to-run transition (WRT). The contribution of the iliopsoas muscle (IL) in gait transition has not been clarified and explored enough, despite its major role in hip flexion and to control the swing leg. We aimed to determine the role of the IL and major leg muscles on the WRT. Twenty healthy young males walked and ran at 60%, 80%, 100%, 120% and 140% of their WRT-speed. To determine each individual WRT-speed, subjects started walking at 1.25 m/s and the speed was increased 0.1 m/s every 30 s, until they started running, and this speed was considered their WRT-speed.We analyzed surface electromyography (sEMG) of the IL, rectus femoris (RF), biceps femoris (BF), gluteus medius (GMed), tibialis anterior (TA), gastrocnemius (GAS) and soleus (SOL), in walking and running at the same speeds around the WRT. Major electromyography activity changes were found in IL, RF and TA for walking faster than the WRT-speed. Peaks of activity were significantly higher in walking than in running. Larger activation of IL, RF and TA is required to keep up with the increasing speed while maintaining walking pattern. These results underscore the importance of these muscles, especially the IL, to provide a powerful hip flexion to quickly bring the leg forward when walking at high speeds. However, when running at the same speeds, sEMG peaks of the IL are significantly lower. Such an activation pattern is also found in other muscles, suggesting that if certain muscles exceed an activation threshold this may trigger the transition from walk to run. Moreover, the abnormally high IL peaks at higher walking speeds could elicit high forces at the muscle insertions, which should be considered in the design of exercise or rehabilitation protocols.